Organizational impacts of the industrial metaverse - Nir Kshetri (International Telecommunications Society (ITS), 2023)
Many industry analysts have argued that the metaverse's true transformative potential is likely to be realized in the industrial context. This paper provides a detailed analysis and description of the industrial metaverse ecosystem in terms of tools, data, and people and the interplay between them. We analyze multiple case studies of eight companies that have incorporated the industrial metaverse in manufacturing, logistics and other activities. The cases include companies in retail as well as non-retail sectors with different levels of implementation of industrial metaverse solutions. The article advances our understanding of how industrial metaverse can contribute to strategic objectives of companies related to cost, quality, delivery responsiveness to the customer, flexibility, innovation and sustainability.
Keywords: 330; artificial intelligence; digital twin; industrial metaverse; Omniverse; sustainability